The Need for a Rational Utlisation of the Montane Temperate Forests of South India - Wilson, J. (Indian Forester, 1973)
The paper outlines a brief description of the montane temperate lands of South India. Blue Gum and Black Wattle were introduced into these regions as early as in 1843. Due to their quick growth and industrial possibilities, extensive plantations have been raised during the recent past. Details of the industries established for the utilisation of the wood and bark exploited from these plantations are furnished. A survey is made of the requirements of each industry and the expansion programmes they have on hand with reference to market needs. The writer highlights the glaring gap between the demand and the availability of raw materials. The position is rather difficult in the context of few areas available for future extension of plantations of Blue Gum and Wattle in the South and the impossibility of growing them in the North. Suggestions are therefore made for a rational utilisation of the limited land available. While this would include attempts at increasing the area under plantation wherever possible, intensification of the practices now followed is emphasised in order to make these man made forests more productive.